2007
DOI: 10.1167/iovs.07-0269
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Accommodative Facility in Myopes

Abstract: During distance accommodative facility testing, myopes exhibited a lower velocity of accommodation and disaccommodation, which led to a lower distance accommodative facility rate. For near facility measurements, however, although velocity of disaccommodation was lower in myopes, velocity of accommodation was found to be similar in the two refractive groups. A variety of factors that contribute to these differences are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 34 publications
1
63
0
Order By: Relevance
“…Moreover, they speculated that accommodative facility might be a good predictor of future myopic progression. More recently, Radhakrishnan et al 34 reported a similar finding. Thus, taken together, these findings suggest that blur processing at distance may be less effective in myopes, along with slowed near-tofar dynamics.…”
Section: Discussionmentioning
confidence: 64%
“…Moreover, they speculated that accommodative facility might be a good predictor of future myopic progression. More recently, Radhakrishnan et al 34 reported a similar finding. Thus, taken together, these findings suggest that blur processing at distance may be less effective in myopes, along with slowed near-tofar dynamics.…”
Section: Discussionmentioning
confidence: 64%
“…Two of these studies used patients with asthenopia (Liu et al, 1979; Bobier & Sivak, 1983), two used normal subjects (Radhakrishnan et al, 2007; Allen et al, 2010) and one measured the change in accommodation over a one week period with no explicit vision training (Randle & Murphy, 1974). …”
Section: Discussionmentioning
confidence: 99%
“…Bobier and Sivak (1983) made similar measurements on four subjects with accommodative infacility and provided them with VT until they achieved normal flipper rates. Radhakrishnan, Allen and Charman (2007) used a PowerRefractor to measure the difference in accommodative facility between emmetropes and myopes and Allen, Charman and Radhakrishnan (2010) used the same method to objectively measure changes in the dynamics of accommodation after three days of VT in normal subjects. None of these studies measured the effect of training on accommodative vergence or the possible role of vergence-accommodation in improvements in accommodative facility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AF assessment allows the evaluation of the ability of the visual system to perform sudden jumps of accommodation at a determined distance, effectively, progressively, quickly, and comfortably, under monocular and binocular conditions …”
Section: Methodsmentioning
confidence: 99%